Tantangan Pembangunan Sumber Daya Manusia Di Aceh - Yuda Perwira (Jurnal Transformasi Administrasi, 2017)
Human resource is the main capital of development in a region. A reliable human resource is needed to encourage regional development. However, human development always encounter challenges. Aceh Province is one of the provinces in Indonesia that countinously face the challenges of human development when attempting reaching development goals. Thus, this study aims to determine the challenges those may encoutered by Aceh government regarding improving the quality of human development in Aceh. This study uses descriptive analysis for secondary data and some literature study. The results indicates that there is a huge disparity of Human Development Index among regions in Aceh. It may be caused by weakness of coordination in human development policy and strategies among regions. In addition, there are three potential threats to human development, one of them is a high poverty rate. Poverty complicates development because it weakens the level of community participation and illustrates low welfare. In addition, the issues of public spending, such as realization, are a huge barrier for human development in Aceh. Therefore, some strategies must be taken immediately to improve the quality of development such as reducing poverty, improving the quality of education, and introducing health promotion models in Aceh.